Entrepreneurial action - Corbett, Andrew C.; Katz, Jerome A. (Advances in entrepreneurship, firm emergence and growth ;, 2012)
Volume 14 addresses the central issue of entrepreneurial action: while many factors are important to the phenomenon of entrepreneurship, entrepreneurship does not happen until someone takes action! Leading scholars address this through cutting edge thinking on entrepreneurial action via concepts such as 'world-making' and entrepreneurial agency. Two empirical chapters examine how conditions of uncertainty shape the action that underlies opportunity creation and how specific venture creation actions effect nascent entrepreneurial efforts. An integrative model of the cognitive processes provides new insights regarding the importance of inflection points. The role of institutions in entrepreneurial action is examined in the case of state-sponsored social protection and university-based technology transfer systems. Applying effectual and linear models of entrepreneurial action in college classrooms is also explored. The final chapter examines the conceptual foundations and research challenges that lie ahead for scholars investigating entrepreneurial action.